Surface treatment method for improving corrosion resistance of eutectic high-entropy alloy and treated eutectic high-entropy alloy

Through the process flow of pretreatment, ultrasonic impact and post-treatment, the selective corrosion problem of eutectic high-entropy alloy is solved, which significantly improves its corrosion resistance and service life, avoids defects in the laser remelting process, and realizes the material surface Improved fine grain structure and passivation ability.

CN119194323AActive Publication Date: 2024-12-27XIAN UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411167385.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-27
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

Eutectic high-entropy alloys have selective corrosion problems in liquid phase environments, resulting in shortening of the service life of the material. The existing aging treatment and laser surface remelting processes are difficult to effectively solve, and there are problems such as surface overheating, residual stress and defects.

Method used

Using pretreatment, ultrasonic impact and post-treatment process, cast eutectic high-entropy alloys are polished, degreased and solid solution treatments, and surface grains are refined by ultrasonic impact and passivation layer is generated, followed by aging treatment to Eliminate dislocations and residual stresses and improve corrosion resistance.

Benefits of technology

It significantly improves the corrosion resistance and service life of eutectic high-entropy alloys, avoids defects in the laser remelting process, maintains the fine crystal structure of the surface reinforcement layer, and enhances the passivation ability and electrochemical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194323A_ABST
    Figure CN119194323A_ABST
Patent Text Reader

Abstract

The invention discloses a surface treatment method for improving corrosion resistance of a eutectic high-entropy alloy. The surface treatment method comprises the following treatment processes: pretreatment of an as-cast eutectic high-entropy alloy matrix, pretreatment, n passes of ultrasonic peening and aftertreatment. According to the method, dislocation and residual stress generated by ultrasonic impact treatment can be partially eliminated while the strengthened layer on the surface of the material is kept to have a fine grain structure, and the corrosion resistance of the surface of the sample is improved. The invention further provides the eutectic high-entropy alloy subjected to surface strengthening treatment and prepared through the method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal material surface engineering technology and heat treatment technology, and specifically relates to a surface treatment method for improving the corrosion resistance of a eutectic high entropy alloy, and also relates to a eutectic high entropy alloy with surface strengthening treatment. Background Art

[0002] Eutectic high entropy alloys balance the performance of single-phase high entropy alloys through composite materials, combining materials with different excellent properties to improve the performance defects of single materials. 2.1 As a typical representative of eutectic high entropy alloys with a dual-phase structure of FCC phase and BCC phase, the alloy has a series of excellent properties such as high strength and plasticity at room temperature, good radiation resistance, high wear resistance, high temperature corrosion resistance and thermal stability, and has broad application potential. The main elements of the FCC phase are Fe, Co, and Cr, and the main components of the BCC phase are Ni and Al. The two phases have significant differences in composition and structure, and their chemical potentials are also different. Phase selective corrosion caused by microgalvanic couples occurs during the application process, which seriously reduces the service life of this material.

[0003] The main reason for the selective corrosion is that the Cr element in the FCC phase forms a dense corrosion-resistant passivation layer with a higher corrosion potential, while the Ni and Al oxides in the BCC phase are easily oxidized by Cl - Erosion perforation and low potential, in the liquid environment, FCC acts as the cathode and BCC acts as the anode and is corroded first. It can be seen that reducing the potential difference between phases and a dense passivation film can effectively alleviate selective corrosion, and homogenizing the elements between phases can effectively solve the above two problems. Both aging treatment and surface remelting processes can make the elements between phases diffuse with each other, but in terms of corrosion resistance, the improvement of aging treatment is limited. Laser surface remelting can generate a surface passivation layer, which has a significant effect on improving corrosion resistance, but there are defects such as surface overheating, residual stress, pores, inclusions, cracks, etc. Its principle is to improve the surface corrosion resistance of the material by surface grain refinement. Summary of the invention

[0004] The first object of the present invention is to provide a surface treatment method for improving the corrosion resistance of eutectic high entropy alloys. This method can partially eliminate the dislocations and residual stresses generated by ultrasonic impact treatment while maintaining the fine-grained structure of the material surface strengthening layer, thereby improving the corrosion resistance of the sample surface.

[0005] The second object of the present invention is to provide a surface-strengthening treated eutectic high entropy alloy, which has strong corrosion resistance and stable mechanical properties.

[0006] The first technical solution adopted by the present invention is a surface treatment method for improving the corrosion resistance of eutectic high entropy alloys, which adopts the following treatment process: pretreatment of the cast eutectic high entropy alloy matrix → pretreatment → ultrasonic impact n times → post-treatment.

[0007] The present invention is also characterized in that:

[0008] The cast eutectic high entropy alloy is prepared by vacuum arc melting technology and remelted more than 5 times.

[0009] The specific process of pre-treating the cast eutectic high entropy alloy matrix is ​​as follows: grinding and polishing the cast eutectic high entropy alloy, placing it in a degreasing agent, heating it at 50°C to 70°C for 10min to 30min to degrease it, washing it with distilled water, and finally washing it with anhydrous ethanol and drying it;

[0010] The degreasing agent is alkaline, pH=9-11, the solvent in the degreasing agent is deionized water, and the solutes and corresponding molar concentrations in the degreasing agent are: 0.25mol / L-1mol / L sodium hydroxide, 0.1mol / L-0.2mol / L sodium phosphate, and 0.05mol / L-0.1mol / L sodium silicate.

[0011] The specific process of pretreatment is: heating the alloy obtained after pretreatment to 800℃~1200℃ in the furnace, with a heating rate of 5℃ / min~15℃ / min, keeping warm for 1h~5h, and then quenching in water at 25±5℃.

[0012] The specific process of ultrasonic impacting for n times is as follows: ultrasonic impacting the pre-treated alloy surface for n times continuously, where 1≤n≤50;

[0013] The specific process of continuous impact is as follows: the punch moves point by point on the alloy surface after pre-treatment, and the relative movement speed between the alloy surface and the punch in the X direction is 1mm / s~5mm / s. When the punch moves to a predetermined distance in the X direction, it returns, and moves 1mm~4mm in the Y direction each time it returns. The end of an impact stroke is recorded as a pass, and this is repeated n times; the impact frequency of the ultrasonic equipment used is 5kHz~20kHz, the output power is 0.5kW~1.5kW, the ultrasonic impact punch is hemispherical, the ball diameter is 3mm~5mm, and the material of the punch is tungsten carbide cemented carbide.

[0014] The specific process of post-treatment is: put the alloy after ultrasonic impact into a box furnace with a temperature of 500°C to 900°C, keep it warm for 12h to 100h, and cool it with the furnace.

[0015] The second technical solution adopted by the present invention is that the eutectic high entropy alloy with surface strengthening treatment is prepared by the above method.

[0016] The beneficial effects of the present invention are:

[0017] The method of the present invention is to use a cast eutectic high entropy alloy (such as AlCoCrFeNi 2.1 ) as raw materials, and a highly corrosion-resistant strengthened surface was prepared on the alloy surface through ultrasonic impact strengthening treatment. The surface strengthening layer significantly improved the corrosion resistance potential of the material, reduced the corrosion current density, and increased the corrosion resistance. At the same time, the treatment method basically eliminated the phase-selective corrosion caused by micro-galvanic in the cast eutectic high-entropy alloy, inhibited the occurrence of local corrosion, and effectively improved the stability and service life of the cast eutectic high-entropy alloy. The surface strengthening treatment method is simple in process and easy to operate, and can be promoted for industrial use. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the path of ultrasonic impact on the alloy surface in Example 3 of the present invention;

[0019] Figure 2 Eutectic high entropy alloy AlCoCrFeNi after ultrasonic shock strengthening in Example 3 of the present invention 2.1 -XRD pattern of S3;

[0020] Figure 3 The untreated cast AlCoCrFeNi in Example 3 of the present invention 2.1 Cross-sectional SEM image of eutectic high entropy alloy matrix;

[0021] Figure 4 Eutectic high entropy alloy AlCoCrFeNi after ultrasonic shock strengthening in Example 3 of the present invention 2.1 -SEM image of the cross section of S3;

[0022] Figure 5 In Example 3 of the present invention, the cast AlCoCrFeNi 2.1 With AlCoCrFeNi 2.1 -Potentiometric polarization curve of S3 alloy in 3.5% NaCl solution;

[0023] Figure 6 The cast AlCoCrFeNi in Example 3 of the present invention 2.1 With AlCoCrFeNi 2.1 -Electrochemical impedance spectroscopy of S3 alloy in 3.5% NaCl solution. DETAILED DESCRIPTION

[0024] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0025] The present invention provides a surface treatment method for improving the corrosion resistance of a eutectic high entropy alloy. The process is as follows: pre-treating a cast eutectic high entropy alloy substrate → pre-treatment (such as solution treatment) → ultrasonic impact n times (1≤n≤50) → post-treatment (such as aging treatment). The specific steps are as follows:

[0026] (1) Cast eutectic high entropy alloy (such as AlCoCrFeNi 2.1 ) The substrate is pretreated, specifically: the cast eutectic high entropy alloy is polished, placed in a degreasing agent, heated at 50°C to 70°C for 10min to 30min to degrease, washed with distilled water, and finally washed with anhydrous ethanol and dried;

[0027] Among them, the cast eutectic high entropy alloy is prepared by vacuum arc melting technology and remelted more than 5 times;

[0028] The degreasing agent is alkaline, pH=9-11, the solvent in the degreasing agent is deionized water, and the solutes and corresponding molar concentrations in the degreasing agent are: 0.25mol / L-1mol / L sodium hydroxide, 0.1mol / L-0.2mol / L sodium phosphate, 0.05mol / L-0.1mol / L sodium silicate;

[0029] (2) pre-treating the alloy obtained in step (1), i.e., solution treatment, to improve the plasticity of the material, specifically: heating the pre-treated alloy obtained in step (1) to 800° C. to 1200° C. in a furnace at a heating rate of 5° C. / min to 15° C. / min, keeping the temperature for 1 h to 5 h, and then quenching in water at 25±5° C.;

[0030] (3) using ultrasonic impact to continuously impact the alloy surface after pretreatment in step (2) for n (1≤n≤50) passes; wherein the specific process of continuously impacting n times is as follows: the punch moves point by point (such as S-shaped) on the alloy surface after pretreatment, and the relative movement speed between the sample surface and the punch in the X direction is 1 mm / s to 5 mm / s. When the punch moves to a predetermined distance in the X direction, it returns, and moves 1 mm to 4 mm in the Y direction each time it returns. The end of one impact stroke is recorded as one pass, and this is repeated for n times; the impact frequency of the ultrasonic equipment used is 5 kHz to 20 kHz, the output power is 0.5 kW to 1.5 kW, the ultrasonic impact punch is hemispherical, the ball diameter is 3 mm to 5 mm, and the material of the ultrasonic impact punch is tungsten carbide cemented carbide;

[0031] (4) performing post-treatment, namely, aging treatment, on the alloy after ultrasonic impact in step (3), specifically, placing the alloy after ultrasonic impact in a box furnace at a temperature of 500° C. to 900° C., keeping the temperature for 12 h to 100 h, and cooling with the furnace.

[0032] The present invention also provides a surface-strengthened eutectic high entropy alloy (such as AlCoCrFeNi 2.1 ), obtained by the above-mentioned ultrasonic impact strengthening treatment method, its surface strengthening layer exhibits excellent corrosion resistance characteristics and the mechanical properties are stable and not reduced.

[0033] Example 1

[0034] A surface treatment method for improving the corrosion resistance of eutectic high entropy alloy is as follows: 2.1 The eutectic high entropy alloy matrix is ​​pre-treated → pre-treatment → ultrasonic impact n times → post-treatment, and the specific method is as follows:

[0035] (1) Cast AlCoCrFeNi 2.1 The eutectic high entropy alloy matrix was cut into samples of 50 mm × 50 mm × 5 mm, and then pretreated. The pretreatment was as follows: the cast eutectic high entropy alloy was polished, placed in a degreasing agent, heated at 60 ° C for 20 min to remove oil, washed with distilled water, and finally washed with anhydrous ethanol and dried;

[0036] Among them, the cast eutectic high entropy alloy was prepared by vacuum arc melting technology and remelted five times;

[0037] The degreasing agent is alkaline, pH=10, the solvent in the degreasing agent is 100mL of deionized water, and the solutes and corresponding molar concentrations in the degreasing agent are: sodium hydroxide 0.5mol / L, sodium phosphate 0.1mol / L, sodium silicate 0.05mol / L;

[0038] (2) pre-treating the alloy obtained in step (1), i.e., solution treatment, to improve the plasticity of the material, specifically: heating the pre-treated alloy obtained in step (1) to 900° C. in a furnace at a heating rate of 5° C. / min, keeping the temperature for 4 h, and then quenching in water at 30° C.;

[0039] (3) using ultrasonic impact to impact the alloy surface after pretreatment in step (2) for 5 consecutive passes; wherein the specific process of the 5 consecutive impacts is as follows: the punch moves in an S-shaped point-by-point manner on the alloy surface after pretreatment, and the relative movement speed between the sample surface and the punch in the X direction is 1 mm / s. When the punch moves to a predetermined distance in the X direction, it returns, and moves 3 mm in the Y direction each time it returns. The end of one impact stroke is recorded as one pass, and this is repeated for 5 passes; the impact frequency of the ultrasonic equipment used is 15 kHz, the output power is 1 kW, the ultrasonic impact punch is hemispherical, the ball diameter is 4 mm, and the material of the ultrasonic impact punch is tungsten carbide cemented carbide;

[0040] (4) performing post-treatment on the alloy after ultrasonic impact in step (3), namely, aging treatment, specifically, placing the alloy after ultrasonic impact in a box furnace at a temperature of 600° C., keeping the temperature for 80 hours, and cooling with the furnace.

[0041] Example 2

[0042] A surface treatment method for improving the corrosion resistance of eutectic high entropy alloy is as follows: 2.1 The eutectic high entropy alloy matrix is ​​subjected to pretreatment → pretreatment → ultrasonic impact n times → post-treatment;

[0043] (1) Cast AlCoCrFeNi 2.1 The eutectic high entropy alloy matrix was cut into samples of 50 mm × 50 mm × 5 mm, and then pretreated. The pretreatment was as follows: the cast eutectic high entropy alloy was polished, placed in a degreasing agent, heated at 50 ° C for 30 min to remove oil, washed with distilled water, and finally washed with anhydrous ethanol and dried;

[0044] Among them, the cast eutectic high entropy alloy was prepared by vacuum arc melting technology and remelted 6 times;

[0045] The degreasing agent is alkaline, pH=11, the solvent in the degreasing agent is 100mL of deionized water, and the solutes and corresponding molar concentrations in the degreasing agent are: sodium hydroxide 0.8mol / L, sodium phosphate 0.15mol / L, sodium silicate 0.1mol / L;

[0046] (2) pre-treating the alloy obtained in step (1), i.e., solution treatment, to improve the plasticity of the material, specifically: heating the pre-treated alloy obtained in step (1) to 1200° C. in a furnace at a heating rate of 12° C. / min, keeping the temperature for 2 h, and then quenching in water at 25° C.;

[0047] (3) using ultrasonic impact to impact the alloy surface after pretreatment in step (2) for 10 consecutive passes; wherein the specific process of impacting 10 consecutive passes is as follows: the punch moves in an S-shaped point-by-point manner on the alloy surface after pretreatment, and the relative movement speed between the sample surface and the punch in the X direction is 5 mm / s. When the punch moves to a predetermined distance in the X direction, it returns, and moves 1 mm in the Y direction each time it returns. The end of one impact stroke is recorded as one pass, and this is repeated 10 times; the impact frequency of the ultrasonic equipment used is 20 kHz, the output power is 1.5 kW, the ultrasonic impact punch is hemispherical, the ball diameter is 5 mm, and the material of the ultrasonic impact punch is tungsten carbide cemented carbide;

[0048] (4) performing post-treatment on the alloy after ultrasonic impact in step (3), namely, aging treatment, specifically, placing the alloy after ultrasonic impact in a box furnace at a temperature of 900° C., keeping the temperature for 24 hours, and cooling with the furnace.

[0049] Example 3

[0050] A surface treatment method for improving the corrosion resistance of eutectic high entropy alloy is as follows: 2.1 The eutectic high entropy alloy matrix is ​​subjected to pretreatment → pretreatment → ultrasonic impact n times → post-treatment;

[0051] (1) Cast AlCoCrFeNi 2.1 The eutectic high entropy alloy matrix was cut into samples of 50 mm × 50 mm × 5 mm, and then pretreated. The pretreatment was as follows: the cast eutectic high entropy alloy was polished, placed in a degreasing agent, heated at 70 ° C for 15 min to remove oil, washed with distilled water, and finally washed with anhydrous ethanol and dried;

[0052] Among them, the cast eutectic high entropy alloy was prepared by vacuum arc melting technology and remelted 6 times;

[0053] The degreasing agent is alkaline, pH=9, the solvent in the degreasing agent is 100mL of deionized water, and the solutes and corresponding molar concentrations in the degreasing agent are: sodium hydroxide 0.25mol / L, sodium phosphate 0.1mol / L, sodium silicate 0.05mol / L, 100mL of deionized water;

[0054] (2) pre-treating the alloy obtained in step (1), i.e., solution treatment, to improve the plasticity of the material, specifically: heating the pre-treated alloy obtained in step (1) to 1000° C. in a furnace at a heating rate of 5° C. / min, keeping the temperature for 3 h, and then quenching in water at 25° C.;

[0055] (3) The alloy surface after the pretreatment in step (2) is subjected to continuous ultrasonic impact for 20 times; wherein the specific process of continuous impact for 20 times is as follows: the punch performs an S-shaped point-by-point motion on the alloy surface after the pretreatment, such as Figure 1 As shown, the relative movement speed between the sample surface and the punch in the X direction is 5 mm / s. When the punch moves to a predetermined distance in the X direction (determined according to the sample size), it returns. Each time it returns, it moves 1 mm in the Y direction. The end of one impact stroke is recorded as one pass, and this is repeated 20 times. The impact frequency of the ultrasonic equipment used is 5 kHz, the output power is 1.5 kW, the ultrasonic impact punch is hemispherical, the ball diameter is 5 mm, and the material of the ultrasonic impact punch is tungsten carbide.

[0056] (4) The alloy after ultrasonic impact in step (3) is subjected to post-treatment, namely, aging treatment, specifically, the alloy after ultrasonic impact is placed in a box furnace at a temperature of 600° C., kept warm for 24 hours, and cooled in the furnace to obtain a eutectic high entropy alloy with surface strengthening treatment, named AlCoCrFeNi 2.1 -S3.

[0057] Based on the AlCoCrFeNi obtained by treatment in Example 3 2.1 -S3, whose X-ray diffraction pattern and cross-sectional morphology are shown in Figure 2 and Figure 3 As shown. Electrochemical tests were performed on it and AlCoCrFeNi was evaluated from two aspects. 2.1 -S3 corrosion resistance behavior: dynamic potential polarization curve and electrochemical impedance spectroscopy test. According to the test results, the AlCoCrFeNi 2.1 -S3 high entropy alloy corrosion resistance was evaluated. A three-electrode system was used for electrochemical testing, with a saturated calomel electrode as the reference electrode and a Pt electrode as the auxiliary electrode. 2.1 -S3 sample was used as the working electrode and tested in 3.5% NaCl solution.

[0058] Ultrasonic impact treatment is an effective method for surface grain refinement. It generates a passivation layer on the surface without changing the material composition, thereby improving the corrosion resistance of the material and avoiding defects that are easily caused by laser surface remelting. Solution treatment before ultrasonic impact treatment can pre-improve the tensile strength and yield strength of the metal; it can also make the solute elements in the material evenly distributed, reduce the strengthening effect of the grain boundaries, thereby improving the plasticity and toughness of the material, and also avoid the brittle shedding of the material surface strengthening layer due to severe work hardening caused by large-scale plastic deformation during the subsequent continuous ultrasonic impact process. Aging strengthening after ultrasonic impact treatment can precipitate fine Cr-rich particle phases from the supersaturated solid solution to form a passivation film layer with good corrosion resistance. While maintaining the fine-grained structure of the material surface strengthening layer, it can partially eliminate the dislocations and residual stresses generated by ultrasonic impact treatment, thereby improving the corrosion resistance of the sample surface.

[0059] The surface treatment method of this embodiment utilizes ultrasonic impact combined with solution treatment and aging treatment to refine the alloy surface grain size, regulate element distribution, and change the composition of the surface passivation layer, thereby significantly improving corrosion resistance.

[0060] (1) X-ray diffraction

[0061] AlCoCrFeNi 2.1 -The X-ray diffraction pattern of S3 alloy is as follows Figure 2 As shown, the cast AlCoCrFeNi2.1 Alloy and strengthened AlCoCrFeNi 2.1 -S3 alloy has the same diffraction peak position, indicating that the phase composition of the alloy has not changed after surface ultrasonic strengthening, but AlCoCrFeNi 2.1 The diffraction peak intensity of -S3 alloy is significantly reduced, indicating that the ultrasonic impact refines the size of the surface grains, resulting in a decrease in the diffraction peak intensity.

[0062] (2) Cross-sectional morphology

[0063] AlCoCrFeNi 2.1 -S3 alloy cross-sectional morphology scanning electron image Figure 3 , Figure 4 As shown, Figure 3 As cast alloy, Figure 4 AlCoCrFeNi 2.1 -S3 alloy. As can be seen from the figure, both alloys are mainly composed of light gray FCC and dark gray BCC phases, and the two phases form lamellar and cellular eutectic structures. The eutectic structure of the cast alloy is coarser, such as the lamellar spacing is larger. Figure 4 It can be seen that the surface area I has undergone severe plastic deformation, with a thickness of about 15μm, and the eutectic structure has been significantly refined; the eutectic structure in area II has been significantly distorted, which is a deformation buffer layer with a thickness of about 30μm. The refined grains have the characteristics of large specific surface area and high surface activity, which can improve the passivation ability of the material and help enhance corrosion resistance.

[0064] (3) Potentiodynamic polarization test

[0065] AlCoCrFeNi 2.1 The potentiodynamic polarization curve of -S3 alloy in 3.5% NaCl solution is shown in Figure 5 The corrosion potential E is obtained by fitting the curve using the Tafel extrapolation method. corr , corrosion current density I corr and corrosion rate υ, the results are shown in the following table. Figure 5 As can be seen from the results in Table 1, compared with the cast AlCoCrFeNi 2.1 Compared with the alloy, the AlCoCrFeNi 2.1 -S3 alloy has a more positive corrosion potential and a smaller corrosion current density. The average corrosion rate is reduced from 3.3679 mm / a in the cast state to 0.0069 mm / a, indicating that ultrasonic strengthening significantly improves the corrosion resistance of AlCoCrFeNi 2.1 -Corrosion resistance of S3 alloy.

[0066] Table 1 AlCoCrFeNi 2.1Polarization curve fitting parameters of -S3 alloy in 3.5% NaCl solution

[0067]

[0068] (4) Electrochemical impedance spectroscopy (EIS) test

[0069] according to Figure 6 The equivalent circuit diagram shown is Figure 6 The EIS data shown in the figure are fitted, and the fitting results of each circuit element are shown in the following table. Figure 6 As can be seen from the results in Table 2, compared with the cast AlCoCrFeNi 2.1 Compared with the alloy, the AlCoCrFeNi 2.1 -S3 alloy has a large polarization resistance Rp, which increases to 219.1kΩ, indicating that ultrasonic strengthening significantly improves the AlCoCrFeNi 2.1 -Corrosion resistance of S3 alloy.

[0070] Table 2AlCoCrFeNi 2.1 Electrochemical impedance spectroscopy fitting parameters of S3 alloy in 3.5% NaCl solution

[0071]

Claims

1. A surface treatment method for improving the corrosion resistance of a eutectic high entropy alloy, characterized in that: The following processing process is adopted: pretreatment of the cast eutectic high entropy alloy matrix → pretreatment → ultrasonic impact n times → post-treatment.

2. The surface treatment method for improving the corrosion resistance of eutectic high entropy alloy according to claim 1, characterized in that: The cast eutectic high entropy alloy is prepared by vacuum arc melting technology and remelted more than 5 times.

3. The surface treatment method for improving the corrosion resistance of eutectic high entropy alloy according to claim 2, characterized in that: The specific process of pre-treating the cast eutectic high entropy alloy matrix is ​​as follows: grinding and polishing the cast eutectic high entropy alloy, placing it in a degreasing agent, heating it at 50° C. to 70° C. for 10 min to 30 min to degrease it, washing it with distilled water, and finally washing it with anhydrous ethanol and drying it; The degreasing agent is alkaline, pH=9-11, the solvent in the degreasing agent is deionized water, and the solutes and corresponding molar concentrations in the degreasing agent are: 0.25mol / L-1mol / L sodium hydroxide, 0.1mol / L-0.2mol / L sodium phosphate, and 0.05mol / L-0.1mol / L sodium silicate.

4. The surface treatment method for improving the corrosion resistance of eutectic high entropy alloy according to claim 3, characterized in that: The specific process of the pretreatment is: heating the alloy obtained after the pretreatment to 800°C to 1200°C in a furnace at a heating rate of 5°C / min to 15°C / min, keeping the temperature for 1h to 5h, and then quenching in water at 25±5°C.

5. The surface treatment method for improving the corrosion resistance of eutectic high entropy alloy according to claim 4, characterized in that: The specific process of the ultrasonic impact n times is: using ultrasonic impact to impact the pre-treated alloy surface continuously for n times, where 1≤n≤50; The specific process of continuous impact is as follows: the punch moves point by point on the alloy surface after pre-treatment, and the relative movement speed between the alloy surface and the punch in the X direction is 1mm / s~5mm / s. When the punch moves to a predetermined distance in the X direction, it returns, and moves 1mm~4mm in the Y direction each time it returns. The end of an impact stroke is recorded as a pass, and this is repeated n times; the impact frequency of the ultrasonic equipment used is 5kHz~20kHz, the output power is 0.5kW~1.5kW, the ultrasonic impact punch is hemispherical, the ball diameter is 3mm~5mm, and the material of the punch is tungsten carbide cemented carbide.

6. The surface treatment method for improving the corrosion resistance of eutectic high entropy alloy according to claim 5, characterized in that: The specific process of the post-treatment is: putting the alloy after ultrasonic impact into a box furnace with a temperature of 500° C. to 900° C., keeping the temperature for 12 h to 100 h, and cooling with the furnace.

7. A surface-strengthened eutectic high-entropy alloy prepared by the method of any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method for improving surface performance of single-phase high-entropy alloy

    CN109097708A

  • Preparation method of ultralight high-entropy alloy with micro-lattice structure

    CN110344040A

  • Method for ultrasonic rolling surface strengthening laser additive manufacturing of eutectic high-entropy alloy plate

    CN114682800A

  • Surface laser remelting method of high-entropy alloy material and obtained gradient high-entropy alloy material

    CN114703414A

  • Method for improving fatigue performance of eutectic high-entropy alloy through electron beam surface treatment

    CN115584398A